Modelling and experimentation of a continuous nutrient recovery reactor – an assessment of mixing on reactor operation - Natividad-Marin, Leynard; Schneider, Philip A. (Water research (Oxford), 2023)
Phosphorus recovery from human waste will help assure global food security, reduce environmental impact, and ensure effective stewardship of this limited and valuable resource. This can be accomplished by the precipitation of struvite (MgNH4PO4·6H2O) in a two-zone reactor, continuously fed with nutrient-rich hydrolysed urine and a magnesium solution. The solid struvite crystals are periodically "harvested", removing accumulated crystal mass - and therefore recovered nutrients - from the process, and the operating campaign can, in principle, be continuously operated in a batch-continuous operating mode. A previously developed process model is augmented, incorporating two well-mixed volumes (upper zone and lower zone) that are coupled by intermixing forward and back flows. The intermixing back flow is parametrised and, therefore, adjusted for analysis. Crystal linear growth rate is modelled by a simple power-law kinetic, driven by the nutrient solution's saturation index (SI) of struvite. The instantaneous mass transfer rate of struvite constituents from liquid to solid phase is predicted, using the total interfacial area of the crystal population exposed to the well-mixed solution. This model describes a 12-L, laboratory reactor operated in the hybrid batch-continuous mode, although larger reactors could easily be accommodated, subject to their mixing behaviours. Experiments were performed at a 10-hour hydraulic residence time (HRT), which, importantly, is based on the volume of the well-mixed lower zone, since this is the volume of liquid that actively interacts with the suspended struvite crystals. The Mg/P feed molar ratio was varied (0.34, 0.64 and 1.29) to assess Mg feed rate-limiting behaviour. The concentration profiles of elemental P and Mg agree with experimentation, while P and Mg composition in the solid and X-ray diffraction support the production of struvite.Phosphorus recovery from human waste will help assure global food security, reduce environmental impact, and ensure effective stewardship of this limited and valuable resource. This can be accomplished by the precipitation of struvite (MgNH4PO4·6H2O) in a two-zone reactor, continuously fed with nutrient-rich hydrolysed urine and a magnesium solution. The solid struvite crystals are periodically "harvested", removing accumulated crystal mass - and therefore recovered nutrients - from the process, and the operating campaign can, in principle, be continuously operated in a batch-continuous operating mode. A previously developed process model is augmented, incorporating two well-mixed volumes (upper zone and lower zone) that are coupled by intermixing forward and back flows. The intermixing back flow is parametrised and, therefore, adjusted for analysis. Crystal linear growth rate is modelled by a simple power-law kinetic, driven by the nutrient solution's saturation index (SI) of struvite. The instantaneous mass transfer rate of struvite constituents from liquid to solid phase is predicted, using the total interfacial area of the crystal population exposed to the well-mixed solution. This model describes a 12-L, laboratory reactor operated in the hybrid batch-continuous mode, although larger reactors could easily be accommodated, subject to their mixing behaviours. Experiments were performed at a 10-hour hydraulic residence time (HRT), which, importantly, is based on the volume of the well-mixed lower zone, since this is the volume of liquid that actively interacts with the suspended struvite crystals. The Mg/P feed molar ratio was varied (0.34, 0.64 and 1.29) to assess Mg feed rate-limiting behaviour. The concentration profiles of elemental P and Mg agree with experimentation, while P and Mg composition in the solid and X-ray diffraction support the production of struvite.